Pengaruh Time Budget Pressure, Management Pressure, Locus of Control, dan Perilaku Disfungsional - Gunadi, Mulya Tantra; Muliartha, Ketut (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of Time Budget Pressure, Management Pressure, Locus of Control, and Dysfunctional Behavior on Auditor Performance in KAP in Denpasar. This study uses multiple linear regression analysis techniques. The sampling technique used in this study is the saturation sample technique and the total sample obtained is 36 auditor samples in 10 public accounting firms. The results of the study show that time budget pressure has a negative effect on auditor performance, management pressure has a negative effect on auditor performance, and dysfunctional behavior has a negative effect on auditor performance, whereas, locus of control has a positive effect on auditor performance. This shows the increasing time budget pressure, management pressure, and dysfunctional behavior, the auditor's performance will decrease, while the increasing locus of control will increase the auditor's performance. Keywords: Time Budget Pressure; Pressure Management; Locus of Control; Dysfunctional Behavior; Auditor Performance.